Effect of Urease and Nitrification Inhibitors on Heavy Metal Mobility in an Intensively Cultivated Soil - Nicoleta Vicar; Alina Lațo; Iaroslav Lațo; Florin Crista; Adina Berbecea; Isidora Radulov (Agronomy)
Urease and nitrification inhibitors represent ways to reduce nitrogen losses; their presence modifies microbial and enzymatic activity in the soil, affecting pH and organic matter (OM), which in turn affects the mobility of heavy metals. To evaluate the effect of urea with inhibitors, pH, OM content, and pseudo-total and mobile metal content (Cu, Cd, Ni, Pb, Cr, Zn, and Mn) were determined in soil samples fertilized with six different urea variants with inhibitors. The modification in the pseudo-total content of heavy metals following fertilization (%) was as follows: Cu (−39.26 ÷ −8.82), Cd (10.74 ÷ 15.40), Ni (5.76 ÷ 18.84), Pb (−13.30 ÷ 12.46), Cr (−15.55 ÷ 11.60), Zn (35.10 ÷ 162.76), and Mn (−1.32 ÷ 12.17). The pH was situated in the range of 7.05 to 7.17, while OM content showed an average increase of 16%. The determined pollution indicators revealed an accumulation of Zn in the soil. The results showed a trend of accumulation of bioavailable heavy metals, with the greatest increase for Mn (43%). Only in the case of Zn, there was a decrease in mobile content with the lowest value when applying two urease inhibitors and one nitrification inhibitor. Inhibitors modify the OM content and soil pH, influencing the mobility and bioavailability of heavy metals.